Pilot-scale biogas and in-situ struvite production from pig slurry: A novel integrated approach - Yan, Yixin; Kallikazarou, Nomiki; Tzenos, Christos; Kotsopoulos, Thomas A.; Koutsokeras, Loukas E.; Kokkinidou, Despoina A.; Michael, Christodoulos; Constantinides, Georgios; Anayiotos, Andreas; Botsaris, George; Nisiforou, Olympia A.; Antoniou, Maria G.; et al. (My University, 2023)
Excess ammonia produced during the decomposition of nitrogen-rich substrates inhibits the anaerobic digestion (AD) process while it increases the concentration of ammonium nitrogen (NH4+) in the digestate. Digestate is commonly applied to farmland, causing nitrogen loss via runoff and volatilization. Therefore, developing an integrated strategy to promote the overall efficiency of AD systems susceptible to ammonia toxicity events, is worthy of consideration. Herein, a step-feeding approach to combat ammonia toxicity in AD process in which, intermittent rather than continuous substrate feeding was tested. A pilot-scale, mesophilic (37 ± 1 °C), fed-batch AD reactor (working volume ∼ 6.67 m3), was operated as the biomethanation step in a novel biorefinery concept, to recover bioenergy and nutrients (struvite) from pig slurry. The results showed that methane production yield achieved was 89.7 % of the theoretical at high ammonia levels (4.44 g NH4+-N L−1), indicating an efficient AD process under strong ammonia stress. The production rate of precipitate was 4.0 kg t−1 feedstock, while X-Ray Diffraction analysis revealed that purity of struvite crystal was 98 % w/w. Orthorhombic crystals and homogeneous distribution of significant elements (O, P, N, and Mg) in the precipitate were observed through scanning electron microscopy coupled with energy dispersive X-ray analysis. Recoveries of nitrogen and phosphorus were 48.5 % and 68.5 % from the digestate, respectively. Furthermore, the chemical and sanitary (i.e., Escherichia coli, Enterobacteriaceae and Salmonella) indicators of the precipitate were in line with the EU Fertilizer Regulation. Overall, the obtained results indicate that it is possible to establish an integrated efficient nutrient and energy recovery process for the simultaneous production of high-yield biogas and high-purity struvite fertilizer from pig slurry, which could yield a gross profit of 5.79 € t−1 feedstock.
Keywords: Biomethanation; Biorefinery; Circular economy concept; Fed-batch; Nutrients recovery; Organo-mineral fertilizer